Renin as a key enzyme for the integrity of various critical lifefunctions in the humans - Skiander Ali, Dr.; Malik, Zainab Arshad; Naeem, Zahra; Rafiq, Ayesha (IJRDO-Journal of Applied Science, 2017)
Renin Angiotensin System is the complex and old hormone system mainly involved in theregulation of blood pressure. Renin is released by kidney & acts on Angiotensinogen to produceAntiotensin 1 which is converted to Angiotensin II. This Angiotensin II binds to the cells throughspecific receptors i.e. AT1 and AT2 to perform its functions. Renin-angiotensin-aldosteronesystem maintains the amount of hormone angiotensin in body. Juxtaglomerular cells alongwithcAMP are involved in the release and storage of rennin. Function of JG-cells is opposite torelease of calcium. A number of events regulating rennin include substances released to inhibitcalcium, presence of adenylyl cyclase, phosphodiesterases & receptors for renin and gap junctionalong with calcium waves. In pathogenic conditions activity of RAAS components can causediseases of kidney & heart. RAAS is helpful when Angiotensin ll liberates aldosterone and water& Na level in kidneys. Aliskiren, a rennin inhibitor can cause decrease in systolic blood pressureand plasma rennin. In the onset of diabetes, the activation of AngII pathway supports cell growth& its proliferation, apoptosis, oxidative stress generation etc and these all contributes in cardiacremodeling & accelerating atherosclerosis.